Synergistic antitumor effect mediated by a paclitaxel-conjugated polymeric micelle-coated oncolytic adenovirus. (November 2017) - Kasala, Dayananda; Lee, Soo-Hwan; Hong, Jin Woo; Choi, Joung-Woo; Nam, Kihoon; Chung, Yoon Ho; Kim, Sung Wan; Yun, Chae-Ok
Abstract: Combination treatment consisting of oncolytic adenovirus (Ad) and paclitaxel (PTX) is a promising strategy to achieve synergistic antitumor effect. However, a co-administration approach is subject to inherent limitations due to the poor solubility of PTX and chemoresistance of tumor cells. In order to overcome these limitations, an oncolytic Ad expressing a p53 variant (oAd-vp53) that is resistant to p53 inactivation in the tumor microenvironment was complexed with PEGylated and PTX-conjugated polymeric micelle (APP). This approach generated an oAd-vp53/APP complex (176.4 nm in diameter) that could concurrently deliver both oncolytic Ad and the nanoparticulate drug APP to tumors. APP-complexed replication-incompetent Ad (dAd/APP) exhibited 12-fold higher transduction efficiency than naked dAd in coxsackie adenovirus receptor (CAR)-negative cancer cells. This increased efficiency was attributed to more efficient cellular internalization mediated by charge interactions between APP and anionic cell membranes. Furthermore, oAd-vp53/APP elicited synergistically higher cancer cell killing than naked oAd-vp53, APP, or oAd-vp53 in combination with PTX (oAd-vp53 + PTX); this synergistic effect was shown to be due to superior induction of apoptosis and viral replication. Importantly, oAd-vp53/APP induced more potent and synergistic antitumor effect through both local and systemic administration by enhancing replication of oncolytic Ad and induction of apoptosis in tumor tissue. Further, the APP coating on the surface of Ad markedly attenuated the host immune response against Ad and decreased hepatic sequestration, resulting in minimal hepatotoxicity and a good safety profile. These attributes enabled oAd-vp53/APP to elicit potent antitumor effect over multiple treatment cycles. Altogether, we demonstrate that concurrent delivery of oncolytic Ad and APP as a single nanocomplex is a promising strategy for achieving synergistic antitumor effect. Graphical abstract: